1997
DOI: 10.1016/s0014-5793(97)01324-0
|View full text |Cite
|
Sign up to set email alerts
|

DDC‐4, an apoptosis‐associated gene, is a secreted frizzled relative

Abstract: The differential display method has been used in our laboratory as a coincidence analysis to isolate genes expressed in common in each of three different rat tissues undergoing physiological apoptosis: mammary gland, ovarian corpus luteum and ventral prostate. The most interesting of these isolates, DDC-4, shows a clear association with apoptosis, its expression being confined to these three organs, and only during their involution. Using DDC-4 as probe, we screened a rat ovarian cDNA library to obtain full-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 25 publications
2
49
0
Order By: Relevance
“…We have previously shown that DDC-4/sFRP-4 was upregulated in various tissues undergoing physiological apoptosis. 3,4,45 The new data show that DDC-4/sFRP-4 expression is a stimulus rather than a consequence of the apoptotic program in the mammary gland. Since DDC-4 is an sFRP and thus thought to sequester Wnt ligands, we propose a role for DDC-4/sFRP-4 in abrogating a Wnt-regulated survival pathway, the latter possibly signaling via PKB/Akt.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…We have previously shown that DDC-4/sFRP-4 was upregulated in various tissues undergoing physiological apoptosis. 3,4,45 The new data show that DDC-4/sFRP-4 expression is a stimulus rather than a consequence of the apoptotic program in the mammary gland. Since DDC-4 is an sFRP and thus thought to sequester Wnt ligands, we propose a role for DDC-4/sFRP-4 in abrogating a Wnt-regulated survival pathway, the latter possibly signaling via PKB/Akt.…”
Section: Discussionmentioning
confidence: 81%
“…4 The retroviral construct is shown schematically in Figure 1a. Using the BOSC 'helper' packaging cells, 16 retroviral titres of 2 Â 10 5 infectious units/ml were obtained.…”
Section: Establishment Of Cell Lines Overexpressing Ddc-4/ Sfrp-4mentioning
confidence: 99%
See 2 more Smart Citations
“…Secretory Frps were independently isolated from bovine, Xenopus, mouse, rat and human by different laboratories (Hoang et al, 1996; Leyns et al, 1997; Rattner et al, 1997;Wang et al, 1997;Wolf et al, 1997;Zhou et al, 1998;Chang et al, 1999;Yam et al, 1999;Katoh, 2001). The precise interaction of each Frp protein in modulating Wnt signaling remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%